Air pollution inputs to the Mojave Desert by fusing surface mobile and airborne in situ and airborne and satellite remote sensing: A case study of interbasin transport with numerical model validation. (1st March 2020) - Leifer, Ira; Melton, Christopher; Chatfield, Robert; Cui, Xinguang; Fischer, Marc L.; Fladeland, Matthew; Gore, Warren; Hlavka, Dennis L.; Iraci, Laura T.; Marrero, Josette; Ryoo, Ju-Mee; Tanaka, Tomoaki; et al.
Abstract: Deserts are fragile and highly sensitive ecosystems that increasingly are affected by upwind urban areas and industrial activities. The Los Angeles Basin (LAB) contributes to poor air quality in downwind deserts including the Mojave Desert. Few studies have investigated potential air pollution inputs to the Mojave, whose fragile ecosystem includes endangered plant and animal species. Data were collected on 19 August 2015 by a mobile air quality laboratory, AMOG (AutoMObile trace Gas) Surveyor, that observed inputs can arise from the LAB as well as the San Joaquin Valley (SJV), California. The campaign used a strong methane (CH4 ) plume as a tracer for the downwind fate of emissions from Bakersfield area petroleum production and also measured ozone (O3 ). Additional in situ concurrent airborne GHG and O3 data were collected by AJAX - Alpha Jet Atmospheric eXperiment. Both AMOG and AJAX measure winds. Mojave Desert air quality was very poor (visibility ~4 km). Based on the winds, an additional source was inferred beyond the LAB and SJV Basins. Numerical transport modeling and analysis of aerosol lidar data collected the same day by the Cloud Profiling LiDAR onboard the Earth Research-2 stratospheric airplane demonstrated that fires in Northern California were responsible, with prevailing winds transporting air southwards along the eastern Sierra Nevada Range (Bishop Valley) to the Mojave. Whereas the southern and eastern Mojave are impacted by SJV and LAB outflow, the north Mojave generally avoids these inputs. This study shows it can be affected by even distant wildfires, which likely will increase in occurrence and intensity from climate change. Thus, regulatory efforts to reduce air quality impacts on the endangered Mojave ecosystem must include wildfires and also account for the significant differences between different regions of the Mojave. Currently, there is a paucity of studies, highlighting the critical need for field research. Graphical abstract: Image 1 Highlights: Kern oil field's air flows through the Tehachapi Pass to the Mojave Desert. Mojave air quality can be reduced by fire to the north, through the Owens Valley. San Joaquin Valley and Los Angeles and fire pollution mix in the Mojave Desert. Climate change will increase the importance of fire air pollution to the Mojave.